Measuring Floc Structural Characteristics - Jarvis, Peter; Jefferson, Bruce; Parsons, Simon A. (Springer, 2005)
A review is presented of a range of techniques for the structural characterisation of flocs. Flocs may be considered as highly porous aggregates composed of smaller primary particles. The irregular size and shape of flocs makes them difficult to measure and quantify. A range of different equivalent diameters are often used to define the floc size and allow comparison with other floc systems. The application of a range of floc sizing methods has been described. Microscopy is time consuming, requiring large sample size and considerable preparation but gives good information on floc shape and form. Light scattering and transmitted light techniques have been used to good effect to measure floc size on-line whilst individual particle sensors have limited applicability to measuring floc size. Fractal dimension can be measured using one of three major techniques: light scattering, settling and two dimensional (2D) image analysis. Light scattering is ideally suited for small, open flocs of low refractive index whilst settling may be applied to most floc systems of low porosity. 2D image analysis requires flocs to have good contrast between the solid in the floc and the background.